Early termination of a judge's powers as a measure of legal responsibility: problems of legal regulation and law enforcement - I. V. Glazunova; A. V. Nikitina (Правоприменение)
The subject of the study is the theoretical, legislative and practical application problems of the early termination of a judge as a measure of legal responsibility. According to the authors' opinion there are several problems: the lack of scientific and legislative unity on the issue of the sectoral nature of this measure; the unsystematic, uncoordinated nature of legislation and law enforcement practice; the apparent discrepancy of the Law of the Russian Federation “On the Status of Judges in the Russian Federation” (hereinafter - the Status of Judges) which regulates the grounds and procedure for the early termination of the powers of a judge and the practice of its application to the fundamental principles of legal responsibility.The aim of this article is to make recommendations aimed at improving the legal regulation and practice of such a legal liability measure as early termination of the power of the judge.The methodology. The main method of research is the general scientific dialectical method of cognition, using universal scientific methods: analysis and synthesis, induction and deduction, formal-logical and systemic. The specific scientific methods are applied: the formal legal method, the methods of legal modelling and the methods of forecasting.Main results and field of application. The authors concluded that the early termination of a power of judge, for whatever reason, is related to his or her illegal behaviour. It should be explicitly recognized as a measure of legal responsibility in the Status of Judges. It is necessary that the legal grounds for judge early termination meet the requirements of legal certainty. The application of this measure is based on the fundamental principles of legal responsibility: justice, humanism, legal equality, proportionality of the sanction to the degree of social danger of the act committed, individualization of the punishment, etc. The Status of Judges and the Regulation on the functioning of the qualification collegium of Judges should be supplemented by legal provisions governing the procedure for applying to a judge early termination as a measure of legal liability that does not involve the commission of a disciplinary offence. A fair, public and adversarial procedure must be used to ensure that judges in the high and medium courts can terminated early. The rules for this procedure must be laid down in federal constitutional law.Conclusions. The implementation of such proposals would lead to the formation of legislation and the law enforcement practice, consistent with the main principles of legal responsibility and the basic provisions of its theory. It would guarantee the fairness and predictability of decisions towards judges. Ultimately it would ensure an appropriate balance between the independence of judges and their accountability for gross and systematic violations incompatible with the status of judges.